Effect of Kaolin/Defoliation Combined with Dry Ice on Lambrusco Red Wine Production to Constrain the Effects of Climate Change - Montevecchi, G.; Masino, F.; Versari, A.; Ricci, A.; Nigro, G.; Antonelli, A. (South African Journal of Enology and Viticulture, 2021)
Since viticulture is affected considerably by climate change, it is imperative to encourage research on new strategies in order to constrain these critical effects on the composition of berries and the quality of wines. A multi-strategy approach composed of (i) kaolin application on foliage, (ii) late tree defoliation and (iii) cryomaceration of grapes with dry ice was evaluated in the production of Lambrusco Salamino wines. Physical, chemical and sensory analyses were carried out on the sample set, including the control wines. In general, cryomaceration with dry ice proved to be a winning choice to lower alcoholic strength (roughly 5%). In addition, the wines showed an increase in anthocyanin content by approximately 17%, while the content of catechins, flavanols and hydroxycinnamic acids decreased. Consistent with the increase in the anthocyanin content, an increase in colour indices and sensory colour intensity scores was observed. As for the aromatic profile, 2-phenylethanol showed an increase of approximately 18% in the treated wines while, in parallel, a lower content of C6 alcohols and volatile fatty acids was observed. The multiple adaptation strategies put in place in the present study show an alternative way to mitigate the severe effects of climate change on wine production, and to face changing consumer demands.